Exploring the Shadows: Validation of the Short Dark Tetrad (SD4) in Indonesian - Arnietta, Serafina Novianty; Natalya, Lina; Siaputra, Ide Bagus (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The increasing incidence of crime and violence among university students highlights the importance of understanding dark personality traits within social, educational, and workplace contexts. Dark personality traits including Machiavellianism, Narcissism, Psychopathy, and Sadism—play a significant role in interpersonal dynamics, decision-making, and individual adaptation strategies. This study aims to validate the Indonesian version of The Short Dark Tetrad (SD4) scale. A total of 305 students from various faculties at the University of Surabaya participated in this study, selected through purposive sampling. Data were analyzed using Principal Component Analysis (PCA) to assess structural validity and Cronbach’s Alpha to determine reliability. The results indicate that the Indonesian version of SD4 demonstrates adequate internal structural validity, with reliability coefficients ranging from 0.621 to 0.752. These findings suggest that SD4 is a valid and reliable instrument for identifying dark personality traits among Indonesian university students. The implications of this study support the use of SD4 in both academic and practical settings, particularly for psychological assessment and character development in higher education environments. Fenomena kejahatan dan kekerasan yang meningkat di kalangan mahasiswa menunjukkan pentingnya pemahaman terhadap aspek-aspek kepribadian gelap (dark personality) dalam konteks sosial, pendidikan, dan lingkungan kerja. Kepribadian gelap, yang mencakup Machiavellianism, Narsistik, Psikopati, dan Sadisme, memiliki peran penting dalam dinamika interpersonal, pengambilan keputusan, serta strategi adaptasi individu. Penelitian ini bertujuan untuk memvalidasi alat ukur The Short Dark Tetrad (SD4) dalam Bahasa Indonesia. Penelitian melibatkan 305 mahasiswa dari berbagai fakultas di Universitas Surabaya yang dipilih melalui metode purposive sampling. Data dianalisis menggunakan Principal Component Analysis (PCA) untuk menguji validitas struktur dan Cronbach’s Alpha untuk menguji reliabilitas. Hasil penelitian menunjukkan bahwa SD4 versi Bahasa Indonesia memiliki validitas struktur internal yang memadai, dengan nilai reliabilitas berkisar antara 0.621 hingga 0.752. Temuan ini menunjukkan bahwa SD4 merupakan alat ukur yang valid dan reliabel untuk mengidentifikasi kepribadian gelap pada populasi mahasiswa Indonesia. Implikasi dari penelitian ini mendukung penggunaan SD4 dalam konteks akademik dan praktis, terutama dalam pengembangan intervensi psikologis dan pemahaman karakter individu di lingkungan pendidikan tinggi.